Evaluation of corrosion inhibition performance of silica sol–gel layers deposited on galvanised steel. (3rd July 2016) - Cotolan, N.; Varvara, S.; Albert, E.; Szabó, G.; Hórvölgyi, Z.; Mureşan, L.-M.
Abstract : The present work reports a comparative investigation of the electrochemical behaviour of some new types of silica sol–gel coatings with enhanced corrosion resistance deposited on electrolytically or thermally (hot-dip) zinc-coated steel. The coatings were rendered hydrophobic by silylation. Dichlorodimethylsilane or trimethylchlorosilane were used as silylating agents and cetyltrimethylammonium bromide or Pluronic PE 10300, as templating agents. The morpho-structural and optical properties of compact and mesoporous silica coatings were characterised with different methods. The corrosion behaviour of the coatings was evaluated by open circuit potential measurements, Tafel interpretation of the polarisation curves and electrochemical impedance spectroscopy. Both silylating agents improve significantly the corrosion resistance of both porous and compact coatings by reducing the corrosion current density with at least one order of magnitude. The possibility to use the porous structure of the coatings as corrosion inhibitor carriers was explored by loading of mesoporous silica layers with 1 H -benzotriazole.